Kendala-Kendala Dalam Pengajuan Sertifikat Hak Atas Tanah Sempadan Danau Perintis Kab. Bone Bolango (International Forum of Researchers and Lecturers, 2024)
This research aims to find out what the legal procedure is for applying for a title certificate for land bordering the Pioneer Lake District. Bone Bolango and what are the obstacles in applying for a title certificate for land bordering Pioneer Lake District. Bone Bolango. The type of research used is empirical legal research with a sociological juridical research model, a qualitative approach. The research samples were Huluduotamo Village Officials and several community houses on the outskirts of Perintis Lake. Data obtained through primary and secondary data were analyzed qualitatively and then presented descriptively. The results of the research show that the legal procedure for submitting a land title certificate at the Perintis Lake Border, District. BoneBolango, namely Measuring, mapping, land bookkeeping, registration and transfer of land rights as well as providing proof of rights as a strong sign of Bukiti, as well as Obstacles in Applying for Certificates of Land Rights on the Borders of Lake Perintis District. BoneBolango Juridically, this is contrary to article 19 paragraph (2) of the UUPA which states that